HUBUNGAN KEBERMAKNAAN HIDUP DENGAN PENERIMAAN DIRI PADA KAUM WARIA DI YOGYAKARTA - Novi Manja Sari; Indriyati Eko Purwaningsih Purwaningsih (JURNAL SPIRITS, 2012)
ABSTRACTThe purpose of this research is to find out relationship between the meaningfulness of life and self-acceptance of shemale in Yogyakarta. Subject research is 70 of shemales at LSM of Kebaya in Yogyakarta. Data was analyzed by using correlation of product-moment pearson.Collecting data in this research using the meaningfulness of life scale and self-acceptance scale. Self-acceptance scale consisted of 63 items and the meaningfulness of life scale consisted of 53 items.Result of this research show the existence of correlation coefficient equal to 0,402 and mount the signiicancyp=0, 001 (p< 0,05). The hypothesis of this research is accepted, that there is a positive relationship between the meaningfulness of life with self-acceptance. Whereby the higher the meaningfulness of life that is owned by the shemale is the higher the acceptance of himselfÂ Keywords: Self Accceptance, Meaningfulness of Life, Shemale